Prevent Bullying at SDN Margosono as an Implementation of A Safe and Comfortable School Life - Muyassarah Muyassarah; Sawsan Arif Sya’bani; Erick Adisaputra Utama; Dean Muhammad Daffa Karim; Muhammad Danang Nur Romdhoni; Dila Fadhilah; Layla Rosida; Ifany Nur Fatimatuz Zahro; Latisha Putri Anintya (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
As a second home, schools should be a safe and comfortable place for students to gain knowledge. However, a safe and comfortable environment is always overshadowed by a scary specter with the rampant cases of bullying that occur in the school environment. Bullying is an act carried out with the aim of hurting in the form of verbal, physical or psychological by someone who feels strong to someone who is weaker. This is the background to the socialization of bullying prevention at SDN Margosono. With several stages that have been carried out by the community service, it can be obtained that the socialization of bullying prevention can greatly reduce bullying activities that often occur in the school environment. This is proven by the evaluation carried out by the community service after the socialization that there were no more bullying cases because the students themselves understood the forms and impacts of bullying